2001
DOI: 10.1007/s002610000135
|View full text |Cite
|
Sign up to set email alerts
|

Strangulated transomental hernia: CT findings

Abstract: We report a case of surgically confirmed strangulation of small bowel through a defect in the greater omentum. Computed tomography demonstrated the presence and the location of this very unusual internal abdominal hernia. Those findings are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 5 publications
0
22
0
Order By: Relevance
“…Computed tomography has been proposed as a diagnostic modality for the preoperative diagnosis of internal hernias. [15][16][17][18][19][20][21] Blachar et al report CT scan sensitivity of 63%, and specificity of 76% in diagnosing transmesenteric hernias. 17 In this study, 16% of CT scans (n= 4/25) were suspicious for internal hernias, while 88% displayed signs of small bowel obstruction.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Computed tomography has been proposed as a diagnostic modality for the preoperative diagnosis of internal hernias. [15][16][17][18][19][20][21] Blachar et al report CT scan sensitivity of 63%, and specificity of 76% in diagnosing transmesenteric hernias. 17 In this study, 16% of CT scans (n= 4/25) were suspicious for internal hernias, while 88% displayed signs of small bowel obstruction.…”
Section: Discussionmentioning
confidence: 96%
“…However, the CT findings considered to be the predictors of these internal hernias include engorgement of the mesenteric vessels, crowding and stretching of the mesenteric vessels, the whirl sign indicative of small bowel volvulus, right and left displacement of the descending colon, dilatation of the small bowel, presence of a transition zone, and presence of small bowel obstruction. 15,[18][19][20] A delay in surgery, the definitive treatment, leads to the development of gangrenous bowel in a large portion of patients. [10][11][12] Newsome has reported the presence of gangrenous bowel at exploration in 64% of cases (n=9/14).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies have reported the usefulness of CT, especially multi-detector row CT, for the preoperative diagnosis of TOH [2,9,[12][13][14]. In addition to CT signs of small bowel strangulation, (1) a cluster of dilated small bowel loops in the right paracolic gutter (2) medial and posterior displacement of the ascending colon and cecum by dilated loops and (3) absence of omental fat between the dilated loops and anterior abdominal wall, are suggested as characteristic CT findings of TOH [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Transomental (greater or lesser) are rarer still accounting for less than 1% of all internal hernias and are usually a complication of previous surgical procedures. [2][3][4] Small bowel obstruction secondary to an internal hernia is a surgical emergency. Whilst abdominal radiographs and ultrasonography may be of some diagnostic use, CT scanning remains the gold standard.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] Small bowel obstruction secondary to an internal hernia is a surgical emergency. Whilst abdominal radiographs and ultrasonography may be of some diagnostic use, CT scanning remains the gold standard.…”
mentioning
confidence: 99%